Evaluation of Post-PCI Cardiac Patients’ Satisfaction Level with Quality of Care - Paiker Malik, Sarwat; Nadir Khan, Muhammad; Khan Toru, Fahad; Noor, Nighat; Afroz, Misbah; Nazir, Maria (Pakistan Armed Forces Medical Journal, 2025)
Objective: To investigate the patients’ overall satisfaction level with the quality of care provided in those who underwent Percutaneous Coronary Intervention (PCI) and survived an acute coronary syndrome. Study Design: Analytical, Cross-sectional Study. Place and Duration of Study: Armed Forces Institute of Cardiology & National Institute of Heart Diseases, Rawalpindi Pakistan; from Apr to Nov 2023. Methodology: A total of 210 patients, aged over 18 years, were enrolled in the study using non-probability consecutive sampling. The study included individuals with a history of myocardial infarction, prior PCI, hospital stays exceeding 24 hours, and those who were discharged alive. Patients with psychological disorders were excluded from study. Patient satisfaction was measured using a modified version of the Patient Satisfaction Questionnaire (PSQ-III), while the quality of care was assessed through the SERVQUAL framework. Results: Out of 210 patients, 176(83.8%) were males and 34(16.2%) were females and majority of the patients had >60 years of age. One hundred and sixty-four (78.1%) patients were highly satisfied. Median of overall satisfaction level and overall quality of care was 4.00(4.00-4.00) and 4.06(4.06-4.12) respectively. Among demographics, place of residence was in significant association with patient’s satisfaction (p=0.03). Regarding the quality of care, reliability and assurance showed a significant positive correlation with patients’ satisfaction (r=0. 138, p=0.046 and r=0. 163, p=0.018, respectively). Conclusion: Overall the higher satisfaction level was noted in patients with significant positive relationship with empathy and assurance. The greater the quality of care patient receives, the more they are satisfied.